Organizational Politics with Industrial Relation Managers in Pakistani Organizations A Qualitative Exploratory Study - SHAH, SYED QASIM; SURIENTY, DR. LILIS (The journal of contemporary issues in business and government, 2021)
This qualitative exploratory study explores the real life experience of organizational politics from the frame of mind of industrial relations managers. The data was collected from five industrial relations managers and experts who have more than 10 years of experience in the industrial relation field. The study employed a qualitative research design. Research data was extracted from the open ended questions from the participants. The methodology was based on an inductive approach. It was used to explore experiences, opinions and thoughts of the participants. Data were studied for specific themes and then collected into large groups of ideas that delivered information that maintained the themes. For data analysis pattern matching was used. The study explored that the overall perception of organizational politics is unsupportive in industrial relations practices. 60% participant understand that organizational politics is harmful for the organization because it creates hurdles for management rather than providing relief to the employees. The union leaders are trying to create gaps between Management and the workers. Politics between management and non-management staff leads to road block for an organization.